Cultivating Organizational Commitment among Outsourced Workers: A Resource-Based View Perspective - Wibisono, Kunto; Suhariadi, Fendy (Journal of Ecohumanism, 2024)
This study aims to identify and analyze the construction of organizational commitment among outsourced workers through the perspective of Resource-Based View (RBV) theory. Organizational commitment is employees’ orientation towards the company, linking one's identity with the organization. It is crucial due to its strong relationship with employee performance and turnover. This research employs a qualitative descriptive method with a case study approach, focusing on outsourced employees at PT. Mitra Karya Prima. Data were collected through semi-structured interviews and processed using qualitative data analysis techniques. The findings indicate that work environment, individual characteristics, and perceived organizational support (POS) are critical to forming individual commitment. These empirical findings are expected to contribute to developing a model for organizational commitment among outsourced employees and provide managerial insights for formulating policies to enhance field workers’ commitment to the company.